Increasing Vertical Dimension of a Case with Full Mouth Rehabilitation: Case Report. - Radhwan H Hasan; Shilan H Fatah (Erbil Dental Journal)
Introduction: Bruxism is one of the most frequent causes for occlusal tooth wear, with the loss of tooth structure caused by mechanical wear between maxillary and mandibular tooth surfaces, case report was conducted to improve the patient oral health, and to maintain the new vertical dimension since it was lost by teeth clenching.